POTRET RADIKALISASI GERAKAN KEAGAMAAN (Studi Kasus Organisasi GARDAH di Kota Cirebon, Jawa Barat) - Suhanah Suhanah (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
In Indonesia today, Islamic religious movements with radical tendencies have emerged across the country. This paper uses qualitative methods to study the Pagar Aqidah (GARDAH) or the Aqidah Protector organization in Cirebon, a movement that has sought to address issues of apostasy, gambling, the distribution of liquor, and heresy. This study shows that GARDAH is an organization based on the Quran and the Hadith and positions itself as the protector and soldier of the people in the face of Aqidah deviation and wickedness.. In their handling of cases of apostasy, gambling, liquor distribution, and heresy, GARDAH has collaborated with other organizations—particularly Almanar (Aliansi Masyarakat Nahi Munkar/Community Alliance of Wickedness Prevention). Due to their actions in cases of apostasy, some members of GARDAH are now facing legal charges. On the other hand, their attempts to address liquor distribution has led to the closure of liquor distributors. Their actions were further strengthened by the passing of a law that prohibited alcohol in the area by the mayor.